Proceedings of the 2010 ITiCSE Working Group Reports 2010
DOI: 10.1145/1971681.1971685
|View full text |Cite
|
Sign up to set email alerts
|

ITiCSE 2010 working group report motivating our top students

Abstract: It would be unlikely for any first year programming class to be solely composed of novices with the same aptitude for learning. We all have students who arrive with a range of abilities and backgrounds. We have students who barely know their way around a keyboard and those who have programmed professionally; this starting knowledge is also no indicator of learning ability. We need to support struggling students with little knowledge whilst maintaining the enthusiasm of those who are quick to learn, and trying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…The content and context of the courses is important to consider because programming, well-known to be a difficult skill to acquire, is learned by doing, and requires a considerable investment of thought, practice, and motivation to master (Carter et al, 2011;Jenkins, 2001;Settle et al, 2014). Jenkins (2001) found that a considerable portion of the students in an introductory CS course were motivated to learn programming only because it was required.…”
Section: Discussionmentioning
confidence: 99%
“…The content and context of the courses is important to consider because programming, well-known to be a difficult skill to acquire, is learned by doing, and requires a considerable investment of thought, practice, and motivation to master (Carter et al, 2011;Jenkins, 2001;Settle et al, 2014). Jenkins (2001) found that a considerable portion of the students in an introductory CS course were motivated to learn programming only because it was required.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment instruments of different nature can be used to achieve several goals. For example, program comprehension assessment instruments can be used to provide feedback to learners, provide tailored activities to individual learners [46], promote self-regulation and self-reflection oppor-tunities [402], and identify learners at-risk [383]. Some assessment instruments in CER were used to compare learners' performance in program comprehension [195] across institutions.…”
Section: Assessing Program Comprehension Knowledgementioning
confidence: 99%
“…The aims of the CRP course and its learning outcomes are that after completing the course, students should be able to demonstrate the ability to research and develop a software artefact solving a CG research problem (Figure ). A positive side effect, apart from benefiting students in terms of learning and professional development, is that engaging undergraduate students with the type of research more commonly encountered in postgraduate research programmes tends to engage the high achieving students that would otherwise disengage due to a lack of challenge and therefore serves as a complement to the usual educational practice of improving the learning of weaker students [CWF*10]. In the CRP course, the major challenge for students is to deliver not just a software artefact but also a report in the form of an academic paper describing their problem solution by working effectively as part of a team while planning, managing and delivering the project in the given time span.…”
Section: Cg and Animation Undergraduate Research Projectsmentioning
confidence: 99%